2019
DOI: 10.3892/etm.2019.8378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aged garlic extract on arterial elasticity in a placebo‑controlled clinical trial using EndoPAT™ technology

Abstract: Cardiovascular diseases are the main cause of death in the industrialized world, with the main risk factors being elevated blood pressure and blood lipid levels, leading to arterial stiffness and arteriosclerosis. In this study, we examined the effect of aged garlic extract (AGE) on arterial elasticity, using the EndoPAT™ technology in subjects with slightly elevated blood pressure. This randomized double-blind, placebo-controlled clinical trial examined 57 subjects over a period of 12 weeks, with EndoPAT™ mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Nevertheless, no changes were observed in endothelial-relaxation capacity measured by RHI and AI 75 indexes in this study. A similar finding is reported with other garlic extracts [31]. Interestingly, the changes in RHI were higher in subjects with higher initial values of RHI, suggesting that the volunteers that presented a reduced vasodilation capacity after hypoxia would not respond to ABG-extract treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, no changes were observed in endothelial-relaxation capacity measured by RHI and AI 75 indexes in this study. A similar finding is reported with other garlic extracts [31]. Interestingly, the changes in RHI were higher in subjects with higher initial values of RHI, suggesting that the volunteers that presented a reduced vasodilation capacity after hypoxia would not respond to ABG-extract treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Scientific research exploring the medicinal properties of garlic, focuses on allicin, diallyl sulfate and other diallyls ( 1 ). The Allium species, including garlic, contain sulfoxides with unique medicinal properties, including antioxidant ( 2 ), anti-cancer ( 3 ), anti-viral, anti-microbial ( 4 ) and anti-fungal properties ( 5 ), and have been used in the treatment of diabetes ( 6 , 7 ) and periodontal disease ( 8 , 9 ) and for potentially preventing cardiovascular ( 10-12 ) and neurodegenerative diseases ( 13 , 14 ). This great variety in therapeutic properties is the factor that has motivated such extensive research into garlic.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the beneficial effect of AGE on hypertension (8)(9)(10)(11)(12), atherosclerosis (13)(14)(15), metabolic syndrome (16), and gingivitis (17). Furthermore, recent studies have revealed that AGE and its constituents, SAC and S1PC, exert such desirable effects as anti-hypertension (18)(19)(20)(21)(22), cardioprotection (23), antioxidation (24)(25)(26)(27), antiaging (27,28), i m munomodulation (29)(30)(31), a nti-fatig ue (32,33), anti-stress (34,35), anti-inflammation (36)(37)(38)(39), and liver protection (40).…”
Section: Introductionmentioning
confidence: 99%